UPAYA PT. PERKEBUNAN NUSANTARA VIII DALAM MENGEMBANGKAN EKSPOR TEH HITAM KE MALAYSIA - Alvianti Anova; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Indonesian is fifth tea exportir country in the world from volume side after Srilanka, Kenya, Tiongkok and India. Compared than kind of other teas, the black tea is the most produced tea namely about 78%, followed green tea 20% and the rest is oolong tea and white tea namely 2 %. The problem that is faced by PT. Perkebunan Nusantara VIII is many competitors in exporting black tea, both homeland and foreign. In this research the writer uses Independence Liberalism Perspective, it means the interdependence between people and government is influenced by what happens everywhere, by the actor’s action of other countries.Keywords: PT. Perkebunan Nusantara VIII, Black Tea, Ekport